2020
DOI: 10.3390/app10072313
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Generate Vector Beams with Adjustable Amplitude in the Focal Plane

Abstract: We design and investigate an original optical component made of a c-cut uniaxial crystal and an optical system to generate cylindrical vector beams with an adjustable polarization state. The original optical component has a specific, nearly conical shape which allows it to operate like a broadband wave retarder with the fast axis oriented radially with respect to the optical axis. We show via numerical simulations, using the Debye–Wolf diffraction integral, that the focal spot changes depending on the polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This simple case was analyzed in the far field in [30] and we include it here to compare with the next cases. According to Equation (12) the output is…”
Section: Case With Input Circularly Polarized Gaussian Beammentioning
confidence: 99%
See 2 more Smart Citations
“…This simple case was analyzed in the far field in [30] and we include it here to compare with the next cases. According to Equation (12) the output is…”
Section: Case With Input Circularly Polarized Gaussian Beammentioning
confidence: 99%
“…This input state was obtained by illuminating with LCP a static q-plate of q = 1 (Thorlabs WPV10L-633) inserted in the PSG. According to Equation (12) this input RCP vortex beam now provides an output beam given by V out = 1 √ 2…”
Section: Case With Input Circularly Polarized Vortex Beammentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most intriguing phenomena that have been observed for the linearly polarized Laguerre–Gauss beam incident on the optical system is the breaking of the circular symmetry as the beam propagates to the lens’s focal plane. This behaviour is theoretically explained in one of our previous work 31 as well as in Quiceno-Moreno et al 21 to be caused by the Gouy phase shift associated with the propagation of Laguerre–Gauss modes to the focal plane of a lens.…”
Section: Introductionmentioning
confidence: 51%
“…Loussert et al 30 have demonstrated that 100% efficiency can be achieved using a single piece of uniaxial material illuminated by a nearly conical superposition of plane-waves. In addition, a collimated input beam on an optical system consisting of an SPP and a uniaxial crystal with a special shape has been theoretically proven to generate HVBs 31 . Using uniaxial crystals to generate VVBs and HVBs may have some advantages over the other methods, for instance, the possibility to achieve conversion without losses and also to use high power fs pulsed beams.…”
Section: Introductionmentioning
confidence: 99%